The validity of electronic evidence in Omani law - Al-Alawi, Hamad Salem Hamad (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the authenticity of electronic evidence in the Omani Law and the role of the Omani legislation regards the way of dealing with electronic evidence as evidence of proof. To achieve the objective of this study, the descriptive analytical legal approach was used. The results showed that, despite the difficulties encountered by the concerned authorities in the field of criminal proof, the Omani legislator was able to keep up with civilizational progress by enacting laws to regulate electronic evidence. Moreover, the legislation cared about electronic evidence and regulated the way of obtaining it given its importance for criminal proof. The research came up with various recommendations; most notably that it is required to qualify a specialized cadre of judicial officers and electronic crime cases officers by providing courses and practical programs in information technology and methods of getting evidence to be protected from being lost. The recommendations also emphasized the importance of international collaboration in criminal affairs, especially in terms of electronic crimes and collecting electronic evidence.